Expression patterns of mechanosensitive ion channel PIEZOs in irreversible pulpitis - Wenying Yang; Lu Lin; Shucheng Hu; Bin Jiang; Ruhan Yang; Weijun Yu; Jiaqi Tang; Dan Zhao; Yuting Gu; Min Jin; Jin Li; Eryi Lu (BMC, 2024)
Abstract Background Mechanosensitive ion channel PIEZOs have been widely reported to involve inflammation and pain. This study aimed to clarify expression patterns of PIEZOs and their potential relations to irreversible pulpitis. Materials and methods Normal pulp tissues (n = 29) from patients with impacted third molars and inflamed pulp tissues (n = 23) from patients with irreversible pulpitis were collected. Pain levels were assessed using a numerical rating scale. PIEZO expressions were measured using real-time PCR and then confirmed using GEO datasets GSE77459, immunoblot, and immunohistochemistry staining. Correlations of PIEZO mRNA expression with inflammatory markers, pain markers, or clinical pain levels were evaluated using Spearman's correlation analysis. Univariate analysis was conducted to analyze PIEZO expressions based on pain description and clinical examinations of cold test, percussion, palpation, and bite test. Results Compared with normal pulp tissues, mRNA expression levels of PIEZO1 were significantly increased in inflamed pulp tissues, while PIEZO2 was significantly decreased, which was further confirmed in GSE77459 and on a protein and histological level. The positive correlation of the mRNA expression levels between PIEZO1 and inflammatory markers, as well as between PIEZO2 and pain markers, was verified. PIEZO2 expression was also positively correlated with pain levels. Besides, irreversible pulpitis patients who reported continuous pain and who detected a positive response to cold stimulus exhibited a higher expression level of PIEZO2 in the inflamed pulp tissues. By contrast, patients reporting pain duration of more than one week showed a higher expression level of PIEZO1. Conclusions This study demonstrated the upregulation of PIEZO1 and the downregulation of PIEZO2 in irreversible pulpitis and revealed the potential relation of PIEZO1 and PIEZO2 to inflammation and pain. These findings suggested that PIEZOs might play critical roles in the progression of irreversible pulpitis and paved the way for further investigations aimed at novel therapies of irreversible pulpitis by targeting PIEZOs.